Efficacy of sodium valproate in the prophylactic treatment of migraine - Lizárraga Luyo, Juan Fernando (2012)
Introduction: migraine is a chronic recurrent pain syndrome accompanied by neurological features. Objectives: evaluate the efficacy of sodium valproate in the migraine prophylactic, measuring pain intensity and frequency. Material and Methods: prospective, longitudinal, experiemental and randomized in 30 patients, each patient received in the 1st week 1 table/day of 500 mg orally and 2 table/day of 500 mg for the next 7 weeks Results: 97% reported decreased pain intensity. 97% were in category 3 of frequency of migraine attacks per month 0. during the 1 st month of treatment, it was reduced to 0% and remained during the 2nd month. Conclusions: prophylactic treatment of migraine with sodium valproate causes a decrease in pain intensity and frequency.